Brightly Fluorescent 2'-Deoxyribonucleoside Triphosphates Bearing Methylated Bodipy Fluorophore for in Cellulo Incorporation to DNA, Imaging, and Flow Cytometry - Güixens-Gallardo, Pedro; Zawada, Zbigniew; Matyašovský, Ján; Dziuba, Dmytro; Pohl, Radek; Kraus, Tomáš; Hocek, Michal (Bioconjugate chemistry, 2018)
Synthesis of cytosine, uracil, and 7-deazaadenine 2'-deoxyribonucleosides and triphosphates (dNTPs) bearing hexamethylated phenyl-bodipy fluorophore attached at position 5 of pyrimidines or at position 7 of 7-deazapurine was developed. All the title labeled nucleosides and dNTPs displayed bright green fluorescence with very high quantum yields. The modified dNmBdpTPs were good substrates to diverse DNA polymerases and were used for in vitro enzymatic synthesis of labeled DNA by primer extension or PCR. In combination with cationic cyclodextrin-peptide-based dNTP transporter, the dNmBdpTPs were successfully used for staining of genomic DNA in living cells for applications in confocal microscopy and in flow cytometry. The best performing cytosine nucleotide dCmBdpTP was used to monitor mitosis in live cells.
Keywords: metylace; Fluorescent Dyes; cytosin; Cell Line, Tumor; deoxyribonukleosidy; Adenine; průtoková cytometrie; optické zobrazování; polyfosfáty; Polyphosphates; Staining and Labeling; puriny; Cytosine; DNA; lidé; Flow Cytometry; Boron Compounds; barvení a značení; fluorescenční barviva; Optical Imaging; Methylation; adenin; Purines; Deoxyribonucleosides; sloučeniny boru; nádorové buněčné linie; Humans